Digging the compromise: investigating the link between limb bone histology and fossoriality in the aardvark (Orycteropus afer) - Legendre,Lucas J.; Botha-Brink,Jennifer (PeerJ, 2018)
Bone microstructure has long been known as a powerful tool to investigate lifestyle-related biomechanical constraints, and many studies have focused on identifying such constraints in the limb bones of aquatic or arboreal mammals in recent years. The limb bone microstructure of fossorial mammals, however, has not been extensively described. Furthermore, so far, studies on this subject have always focused on the bone histology of small burrowers, such as subterranean rodents or true moles. Physiological constraints associated with digging, however, are known to be strongly influenced by body size, and larger burrowers are likely to exhibit a histological profile more conspicuously influenced by fossorial activity. Here, we describe for the first time the limb bone histology of the aardvark (Orycteropus afer), the largest extant burrowing mammal. The general pattern is very similar for all six sampled limb bones (i.e., humerus, radius, ulna, femur, tibia, and fibula). Most of the cortex at midshaft is comprised of compacted coarse cancellous bone (CCCB), an endosteal tissue formed in the metaphyses through the compaction of bony trabeculae. Conversely, the periosteal bone is highly resorbed in all sections, and is reduced to a thin outer layer, suggesting a pattern of strong cortical drift. This pattern contrasts with that of most large mammals, in which cortical bone is of mostly periosteal origin, and CCCB, being a very compliant bone tissue type, is usually resorbed or remodeled during ontogeny. The link between histology and muscle attachment sites, as well as the influence of the semi-arid environment and ant-eating habits of the aardvark on its bone microstructure, are discussed. We hypothesize that the unusual histological profile of the aardvark is likely the outcome of physiological constraints due to both extensive digging behavior and strong metabolic restrictions. Adaptations to fossoriality are thus the result of a physiological compromise between limited food availability, an environment with high temperature variability, and the need for biomechanical resistance during digging. These results highlight the difficulties of deciphering all factors potentially involved in bone formation in fossorial mammals. Even though the formation and maintaining of CCCB through ontogeny in the aardvark cannot be unambiguously linked with its fossorial habits, a high amount of CCCB has been observed in the limb bones of other large burrowing mammals. The inclusion of such large burrowers in future histological studies is thus likely to improve our understanding of the functional link between bone growth and fossorial lifestyle in an evolutionary context.
Keywords: Bone histology; Aardvark; Fossoriality; Mammals; Environmental constraints